Pemilihan Transmisi Bus Untuk Mendapatkan Konsumsi Bahan Bakar Ideal Berdasarkan Kecepatan Tiap Roda Gigi (P3M Politeknik Negeri Cilacap, 2020)
The population of vehicles in indonesia, always has increased, this has an impact on oil fuel consumption continue to grow also, reduction of fuel consumption in vehicles can be done by the method of eco driving, one of the methods in eco driving most easily applied is the speed settings, gear position, and the selection of the right type of Transmission, but the information setting the speed and position of the gears on each vehicle is definitively less Thus, do the research to find speed settings and the position of the gear is done. This research was conducted on the analysis of the results of calculation of the Specific fuel consumption of vehicles bus with the variations of the two types of transmissions, to know the pattern of the ride's low Specific fuel consumption and the type of transmission the best of transmissions to two. The results obtained from this study, Specific fuel consumption bus will continue to decline at 1000-1300 rpm, but will slowly climb back on 1400-2300 rpm, while the increase in speed is directly proportional to the increase of rotation of the engine, transmission Type MB GO 190 is the most excellent transmission among other transmission a third because of the difference between the rate ratio in this transmission is not too far away so that fuel is wasted due to a pause on this transmission traction loses a little and acceleration of the vehicle a smooth and fast.